Analysis of cracked plate membrane problem using Metis finite element model - Hung, Nguyen Dang; Ngoc, Tran Thanh (Vietnam Journal of Mechanics, 2002)
A conformable and convergent finite element technique is presented for calculation of stress intensity factors for cracked plate membrane problem, which is based on the formulation of the hybrid displacement finite element method, named "Metis elements". In order to achieve a high convergence, this element is combined with an isoparametric element of Barsoum, in which, the mid-side nodes are moved to quarter-point position. Many examples are numerically tested for evaluation this model, show that the element HSM has a good performance for calculation of stress intensity factors.